Urinary Sediment Microscopy and Correlations with Kidney Biopsy: Red Flags Not To Be Missed. Issue 1 (12th January 2023) - Navarro, David; Fonseca, Nuno Moreira; Ferreira, Ana Carina; Barata, Rui; Góis, Mário; Sousa, Helena; Nolasco, Fernando
Abstract : Abstract : Key Points: Automatic urine analyzers struggle to identify dysmorphic erythrocytes, renal tubular epithelial cells, lipids, crystals, and casts. Those particles are identifiable through manual urinary sediment evaluation and are associated with histologic lesions of interest. Manual urinary sediment evaluation may help to shape the indications for performing a kidney biopsy. Background: Urinary sediment is a noninvasive laboratory test that can be performed by an automated analyzer or manually by trained personnel. Manual examination remains the diagnostic standard because it excels at differentiating isomorphic from dysmorphic red blood cells and identifying other urinary particles such as renal tubular epithelial cells (RTECs), lipids, crystals, and the composition of casts. This study aimed to investigate the prevalence of a complete profile of urinary sediment particles and its associations with histologic lesions on kidney biopsy, regardless of diagnosis. Methods: This was a single-center, observational retrospective study of 131 patients who had contemporary manual urinary sediment evaluation and kidney biopsy. A comprehensive set of urinary particles and histologic lesions were quantified, and their associations were analyzed. Results: In our samples, we found an elevated frequency of findings suggestive of proliferative kidney disease and a low frequency of particles evoking urologic damage. The association of histologic lesions and urinary particles was explored with a multivariate model. We identified urinary sediment characteristics that independently correlated with the presence of some histologic lesions: urinary lipids with mesangial expansion (OR=2.86; 95% confidence interval [95% CI], 1.3 to 6.3), mesangial hypercellularity (OR=2.44; 95% CI, 1.06 to 5.58), and wire loops and/or hyaline deposits (OR=2.89; 95% CI, 1.13 to 7.73); Urinary renal tubular epithelial cells with endocapillary hypercellularity (OR=3.17; 95% CI, 1.36 to 7.39), neutrophils and/or karyorrhexis (OR=4.51; 95% CI, 1.61 to 12.61), fibrinoid necrosis (OR=4.35; 95% CI, 1.48 to 12.74), cellular/fibrocellular crescents (OR=5.27; 95% CI, 1.95 to 14.26), and acute tubular necrosis (OR=2.31; 95% CI, 1.08 to 4.97). Conclusions: In a population of patients submitted to kidney biopsy, we found that the presence of some urinary particles (renal tubular epithelial cells, lipids, and dysmorphic erythrocytes), which are seldom reported by automated analyzers, is associated with active proliferative histologic lesions. In this regard, manual urinary sediment evaluation may help to shape the indications for performing a kidney biopsy.